Genome-Wide Analyses Reveal the Genetic Architecture and Candidate Genes of Indicine, Taurine, Synthetic Crossbreds, and Locally Adapted Cattle in Brazil - Verardo, Lucas Lima; e Silva, Fabyano Fonseca; Machado, Marco Antonio; do Carmo Panetto, João Cláudio; de Lima Reis Faza, Daniele Ribeiro; Otto, Pamela Itajara; de Almeida Regitano, Luciana Correia; da Silva, Luiz Otávio Campos; do Egito, Andréa Alves; do Socorro Maués Albuquerque, Maria; Zanella, Ricardo; da Silva, Marcos Vinicius Gualberto Barbosa (Frontiers in Genetics, 2021)
Cattle population history, breeding systems, and geographic subdivision may be reflected in runs of homozygosity (ROH), effective population size (Ne) and linkage disequilibrium (LD) patterns. Thus, the assessment of this information has become essential to the implementation of genomic selection on purebred and crossbred cattle breeding programs. In this way, we assessed the genotype of nineteen cattle breeds raised in Brazil belonging to taurine, indicine, synthetic crossbreds and Iberian-derived locally adapted ancestries to evaluate the overall LD decay patterns, Ne, ROH and breed composition. We were able to obtain a general overview of the genomic architecture of cattle breeds currently raised in Brazil and other tropical countries. We found that, among the evaluated breeds, different marker densities should be used to improve the genomic prediction accuracy and the power of genome wide association studies. Breeds showing low Ne values indicate a recent inbreeding, also reflected by the occurrence of longer ROH, which demand a special attention in the matting schemes to avoid extensive inbreeding. Candidate genes (e.g., ABCA7, PENK, SPP1, IFNAR1, IFNAR2, SPEF2, PRLR, LRRTM1 and LRRTM4) located in the identified ROH islands were evaluated, highlighting biological processes involved with milk production, behavior, rusticity and fertility. Furthermore, we were successful in obtaining the breed composition regarding the taurine and indicine composition using SNP data. Our results were able to observe in detail the genomic backgrounds that are present in each breed and allowed to better understand the various contributions of the ancestors breeds to the modern breed composition to the Brazilian cattle.